Can middle grade and consultant emergency physicians accurately interpret computed tomography scans performed for head trauma? Cross-sectional study. Issue 8 (22nd July 2009) - Boyle, A; Staniciu, D; Lewis, S; Hugman, A; Bauza-Rodriguez, B; Kirby, D; Scoffings, D
Abstract : Background: There has been an increasing demand for computed tomography (CT) scans of the head following trauma over the past 10 years. This has placed radiology services under pressure. Aims: This study aimed to see whether middle grade and consultant doctors with no particular training in radiology working in the emergency department could interpret CT scans performed for trauma with adequate sensitivity and specificity to allow safe discharge. The secondary aim was to describe which abnormalities, if any, were missed. Methods: Study participants were middle grade and consultant emergency physicians. A comparison was made of the ability to identify any abnormality on CT and a clinically important brain injury on CT, compared with a gold standard of a neuroradiology report. Results: 243 consecutive CT scans performed for trauma were reviewed by 17 doctors, including five consultants. The overall sensitivity and specificity for detecting clinically important brain injuries was 87.8 (95% CI 73.8 to 95.9) and 80.2 (95% CI 75.2 to 85.3), respectively. All the missed abnormalities were around the base of the brain. The most commonly overdiagnosed abnormality was diffuse cerebral oedema. Conclusions: Emergency physicians should not interpret CT scans for trauma without extra training.